Pengaruh Model Discovery Learning Berbantuan Komik Digital terhadap Pemahaman Konsep Norma dalam Kehidupan Siswa Sekolah Dasar - Wawan Shokib Rondli; Yuli Khoirinnida (Journal Prakarsa Paedagogia, 2025)
Understanding the concept of social norms is a crucial foundation in character building for students from elementary school onward. The subject â€œNorma dalam Kehidupanâ€ is often not fully understood by elementary school students because the presentation is abstract and lacks visual aids. This study aims to signify the effect of implementing the Discovery Learning model assisted by digital comic media on elementary school student's understanding of the concept of social norms. This study uses a quantitative approach with a quasi-experimental design of the one-group pretest-posttest type. The research subjects were 27 fifth-grade students at one of the public elementary schools in Grobogan Regency. The research instrument was a multiple-choice test given before and after the treatment. The analysis result showed a gain in the average score from 64.07 in the pretest to 84.81 in the posttest, with a percentage increase of 32.3%. The application of the Discovery Learning model provides space for students to build knowledge through the process of exploration and proof of concept, while digital comic media makes it easier to visualize social norm situations in everyday contexts. The combination of the two has proven effective not only in improving students' conceptual understanding but also in encouraging active involvement and emotional responses to the material. This study shows that discovery-based learning supported by contextual visual media can be a strategic alternative to strengthening social values at the elementary school level.